Gustavo Romanov Salvini e as primeiras preocupações com a adaptabilidade da Língua Portuguesa ao Canto lírico: Breve périplo pela História da Ópera em Portugal do séc. XVIII ao séc. XIX - Sofia Gomes Valente, Tânia (Revista Vozes dos Vales: Publicações Acadêmicas, 2014)
This research started from a prejudice, widespread among the community of lyrical singers, both Portuguese and foreigners, that Portuguese is a difficult language to sing. We decided to try to understand where this prejudice came from and if it made any sense scientifically. The starting point and guideline for this research was Romanov Gustavo Salvini, a singing teacher from the 19th century, pioneer in the concern with the issue of singing in Portuguese, at a time when singing opera in Italian was an almost established practice. By analyzing the development of the Portuguese vocal repertoire until the publication of Salvini’s “Cancioneiro”, we concluded that the origin of the prejudice is not likely to be in the phonetic characteristics of the Portuguese language, so beautiful to sing Fado, but in cultural and historical factors.